176 Clinical research participation in neurology. Issue 6 (27th May 2022) - Jacob, Carmen; Copson, Ellen; Galea, Ian
Abstract : The benefits of clinical research for patients are well recognised. The Royal College of Physicians' recent strategy document 'Benefiting from the research effect' highlights the role of NHS trusts in supporting research activity. Anecdotal evidence suggests that higher recruitment of patients to research studies in oncology compared to neurology is partly driven by a more pro-active approach by oncologists in dis- cussing clinical research participation with their patients. In an ongoing evaluation across NHS neurology and oncology services in a large teaching hospital, we are gathering views from clinical staff regarding their experience, attitudes, training, and barriers in recruiting patients to clinical studies, comparing the two specialities. To gather the patient perspective, hospital attenders from the neurology research setting (specifically the multiple sclerosis Phase III trial MS-STAT2), and from the multiple sclerosis clinical service in the same hospital are being surveyed. Preliminary results suggest that in 23/40 trial neurology patients (57.5%), there was at least one occasion where additional clinical care unrelated to the study was delivered as a result of engagement with research pathway. Comparing neurology to oncology, and neurology research with service settings, will deliver objective data to inform improvements in clinical research participation in neurology. carmen.jacob@uhs.nhs.uk